BLOOD PRESSURE MANAGEMENT WITH THE ESH CARE APP – PRELIMINARY RESULTS. (June 2022) - Siafi, Eirini; Konstantinidis, Dimitrios; Andrikou, Ioannis; Polyzos, Dimitrios; Drogkaris, Sotiris; Manta, Eleni; Tatakis, Fotis; Zammanis, Ioannis; Grigoriou, Kalliopi; Dimitriadis, Kyriakos; Leontsinis, Ioannis; Tsioufis, Konstantinos
Abstract : Objective: Main issues in the treatment of hypertension are the low level of blood pressure (BP) control and the economic burden for health care systems. Mobile application with telemonitoring of BP could contribute to better control and lower costs by reducing office visits. This could be useful nowadays with difficult access to health system due to covid-19. The purpose of this study was to investigate if an innovative management strategy of hypertension, such as the use of ESH care application for smartphones combined with a dedicated platform, could improve hypertension control and replace frequent office visits. Design and method: 30 uncontrolled hypertensive patients, treated or untreated [mean age 53 ± 9 years, mean office BP (OBP) 146.3 ± 6.2 / 92.5 ± 9 mmHg, 53% men, 33% smokers, 23% with hypercholesterolemia] were randomized to the application assisted strategy (AAS) (17 patients), where a mobile phone application was offered to communicate home BP measurements (HBPm), or to regular office visits (13 patients). Patients' BP measurements (HBPm for AAS and OBP for standard care group) were evaluated in 1 and 3 months with treatment titration if uncontrolled. In all patients OBP and ambulatory BP measurement (ABPM) were evaluated in 6 months. Results: In both groups the reduction in OBP and ABPM was significant in 6 months. In the AAS group the reduction in systolic/diastolic OBP and 24 h systolic/diastolic BP in 6 months was -26.5 ± 5.6 / -19.4 ± 8.2 mmHg (p < 0, 001) and -19.6 ± 7.7 / -13.8 ± 4.8 mmHg (p < 0.001), respectively. In the standard care group, the reduction in systolic/diastolic OBP and 24 h systolic/diastolic BP in 6 months was -22.6 ± 9.7 / -9.6 ± 11 mmHg (p < 0.005) and -18.4 ± 6.0 / - 8.8 ± 4.4 mmHg (p < 0.001). In AAS group compared to standard care group there was a greater reduction in 24 h diastolic BP (-13.8 ± 4.8 mmHg vs -8.8 ± 4.4 mmHg, p = 0.016) and in diastolic OBP (-19.4 ± 8.2 mmHg vs -9.6 ± 11.0 mmHg, p = 0.04) Conclusions: The present results indicate that the monitoring of patients through a mobile health tool could be useful in hypertension management as it is correlated with better BP control compared to office visits. The trial is still enrolling patients.